2015
DOI: 10.1210/en.2014-1704
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins Are Mediators of Luteolysis in the Human Corpus Luteum

Abstract: Bone morphogenetic proteins (BMPs), members of the transforming growth factor β (TGFβ) superfamily, play important roles in folliculogenesis in various species; however, little is known about their role in luteal function. In this study, we investigated the expression, regulation, and effects of BMP2, BMP4, and BMP6 in carefully dated human corpora lutea and cultured human luteinized granulosa cells. The mRNA abundance of BMPs was increased in the regressing corpus luteum in vivo (P<.01-.001). Human chorionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 39 publications
(53 reference statements)
2
34
0
Order By: Relevance
“…STAR and HSD3B1) involved in cholesterol transfer into mitochondria and conversion of pregnenolone to progesterone. These induced CLs were further characterised as having reduced expression of LHCGR (required for luteal support; Niswender et al 2007) and VEGFA (a key angiogenic regulator; Robinson et al 2007), together with increased expression of BMP2 (linked to luteolysis in regressing CLs; Nio-Kobayashi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…STAR and HSD3B1) involved in cholesterol transfer into mitochondria and conversion of pregnenolone to progesterone. These induced CLs were further characterised as having reduced expression of LHCGR (required for luteal support; Niswender et al 2007) and VEGFA (a key angiogenic regulator; Robinson et al 2007), together with increased expression of BMP2 (linked to luteolysis in regressing CLs; Nio-Kobayashi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In concert with this study, a study using isolated human pre-antral follicles that compared the expression levels of BMPs in five size-matched populations demonstrated that BMP6 and BMP15 are the most abundantly expressed ligands (Kristensen et al ., 2014). In the human corpus luteum, BMP2, BMP4 and BMP6 are highly expressed in the granulosa-lutein and theca-lutein cells and are involved in the process of luteolysis (Nio-Kobayashi et al ., 2015). …”
Section: Intra-ovarian Bmps and Oocyte–somatic Cell Interactionsmentioning
confidence: 99%
“…(2013)BMP6Luteinized GCmRNA & ProteinRT-qPCR, IHCKhalaf et al . (2013)CLmRNA & ProteinRT-qPCR, IHCNio-Kobayashi et al . (2015)BMP7Luteinized GCmRNA & ProteinRT-qPCR, IHCKhalaf et al .…”
Section: Intra-ovarian Bmps and Oocyte–somatic Cell Interactionsmentioning
confidence: 99%
See 2 more Smart Citations